The correlation of nutrition knowledge with dietary diversity and nutritional status of pregnant women - Putra, Muh. Guntur Sunarjono; Kustiyah, Lilik; Dewi, Mira (Jurnal Gizi dan Dietetik Indonesia (Indonesian Journal of Nutrition and Dietetics), 2024)
Background: The mortality rate among pregnant women has witnessed an escalation in both Indonesia and West Java. One contributing factor to this phenomenon is maternal malnutrition or chronic energy deficiency, exerting detrimental effects on both the developing fetus and the expectant mother.Objectives: This study examined the correlation of nutrition knowledge,  dietary diversity, and nutritional status of pregnant women.Methods: This study used a cross-sectional design with 40 pregnant women as subjects using a simple random sampling technique in the working area of the Cikembar Community Health Center, Sukabumi Regency. Data collection was carried out from February 21 to March 3, 2019. The variables studied in this study consisted of subject and socio-economic characteristics, anthropometry of pregnant women, nutritional knowledge, and food consumption, which were assessed using multiple 24-hour recalls. The statistical tests used include descriptive and bivariate tests using the Spearman Test.Results:  The prevalence of CED pregnant women was 52.5%, the level of nutritional knowledge was moderate (47.5%), and food consumption was not diverse (45.0%). There is a significant correlation between nutritional knowledge and diet quality in mothers, reflected in the diversity of food consumption (p= 0.032; r= 0.340). There was also a significant correlation between nutritional knowledge, BMI before pregnancy (p= 0.032; r= 0.339), and MUAC (p= 0.016; r= 0.378).Conclusions: Enhanced nutrition knowledge was associated with improved  dietary diversity, BMI before pregnancy, and MUAC. These outcomes suggest that nutrition and health education pertaining to pregnancy are crucial for prospective mothers to prioritize and enhance.